Study of the design and analytical properties of the lethality neutralization assay used to estimate antivenom potency against Bothrops asper snake venom - Solano Trejos, María Gabriela (2010)
The lethality neutralization assay performed in mice is the standard recommended by the World Health Organization to estimate antivenom potency. The interpretation of its results without considering its analytical capacity may lead to erroneous conclusions. Therefore, laboratories that manufacture or control antivenoms must demonstrate the appropriateness of their models. A study of the method used at Instituto Clodomiro Picado, Costa Rica, to estimate the potency of antivenoms against Bothrops asper snake venom was performed. Results show that venom doses ranging from 2 to 6 Median Lethal Doses (LD50) are appropriate to be used as challenge in this test. Variables such as the injection route, number of mice used per venom/antivenom level, and weight of the animals are critical in the estimation of the Median Effective Dose (ED50), whereas incubation time is not. The assay has an acceptable selectivity, linearity, and limits of detection and quantification. Accuracy of the lethality neutralization assay, expressed as percentage recovery, was between 71% and 127%. Intermediate precision, expressed as relative standard deviation, was ≤17%. It is concluded that the analytical characteristics of this assay are adequate enough to prove product compliance and to have statistical control over an industrial line of antivenom serial production.